The relative correspondence of cranial and genetic distances in papionin taxa and the impact of allometric adjustments. Issue 85 (August 2015) - Smith, Heather F.; von Cramon-Taubadel, Noreen
Abstract: The reconstruction of phylogenetic relationships in the primate fossil record is dependent upon a thorough understanding of the phylogenetic utility of craniodental characters. Here, we test three previously proposed hypotheses for the propensity of primate craniomandibular data to exhibit homoplasy, using a study design based on the relative congruence between cranial distance matrices and a consensus genetic distance matrix ("genetic congruence") for papionin taxa: 1) matrices based on cranial regions subjected to less masticatory strain are more genetically congruent than high-strain cranial matrices; 2) matrices based on cranial regions developing earlier in ontogeny are more genetically congruent than matrices based on regions that develop later; and 3) matrices based on cranial regions with greater anatomical/functional complexity are more genetically congruent than matrices based on anatomically simpler regions. Morphological distance matrices based on the shape of 15 different cranial regions, delineated on the basis of previous catarrhine studies, were statistically compared to a matrix of known genetic distances in papionins. Since sexual dimorphism and allometry are known to characterize this clade, several analytical iterations were conducted: 1) mixed-sex, male-only, and female-only analyses and 2) with and without an allometric scaling adjustment. Across all datasets, the chondrocranium matrix was the most consistently correlated with genetic distances, which is also consistent with previous studies of cercopithecoid taxa; however, there was no support for the internal predictions of the three hypotheses tested. Allometric scaling corrections had the largest impact on the genetic congruence of facial shape matrices, a result consistent with previous studies that have described facial homoplasy in papionin taxa. These findings differ from patterns described for hominoid taxa, suggesting that no single predictive criterion can explain phylogenetic utility of cranial datasets across catarrhine primate taxa. Many of the differences in morphological-genetic matrix correlations could result from different levels of phenotypic integration and evolvability in cercopithecoids and hominoids, suggesting that further study of these phenomena in extant primates is warranted.